X-Rays and Methods for Finding the Linear absorption Coefficient - Karar Karim Miteb Hussein; Duha Qutaiba Ibrahim Saeed; Benin Malek Attia Hadi; Abbas Amer Dakhel Farhan; Asma Mohamed Faisal Mughir (Genius Journals, 2024)
X -rays are electromagnetic waves similar to light waves, except that their wavelengths are limited to A° 0.1 to A° 100, when compared to the lengths of visible waves, which are limited to A° 4000 to A° 7000. When X-rays fall on the material, they are absorbed by the material in three Methods depending on the intensity of incident X-rays. These methods are (Compton scattering - photoelectric effect - pair production)In this research, the linear and mass absorption coefficient of aluminum was found by shining beams of different intensities of X-rays on aluminum strips of different thicknesses. The incident intensity of the Graphic.The results we obtained were highly accurate. The relationship that we obtained between Ln I◦ / I and the fish d was a straight line passing through the origin, meaning that the relationship between them is linear, and from it we obtained the slope, which represents the linear absorption coefficient of the material, which is the portion of the energy absorbed by the fish d. From the readings we obtained, it was observed that the intensity of the window I decreased with the increase in the thickness of the material, D, which indicates the inverse relationship between them, that is, the intensity decreases with increasing thickness. This is due to the absorption of Xrays by the material and thus this beam suffers attenuation.As for the mass absorption coefficient, we obtained it by dividing the linear absorption coefficient by the density of the aluminum material, which is considered a fixed value
Keywords: X-rays; their uses; methods of generation